Social Epidemiology of HIV/TB Co-infection: A Triad with Poverty - Adhikari, Lal Mani (Journal of Advanced Academic Research, 2015)
The dual epidemics of Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) infection are of growing concern in Asia including countries like Nepal. Tuberculosis incidence rates correlate positively with poverty rates and with HIV incidence rates. TB is a leading cause of morbidity and mortality in patients with HIV infections. TB and HIV are commonly known as the diseases of poverty and their co-infection are known to be the deadliest mixture. Social epidemiology of TB and HIV infection reveals that there are more commonalities of risk factors which are associated with poor individual as well as communal socioeconomic status. Poverty is not only a major factor for complexity but also there are more issues associated with social inequality and inaccessibility to health care services. The double burden of TB and HIV pose a serious threat to the people’s health that needs urgent address from health policy makers and health organizations to avert the economic loss in the future. This concept paper concludes that the TB/HIV co-infection is highly linked to an individual’s socio economic status, sociopsychosocial and ecosocial paradigms of disease manifestation and their impact. Journal of Advanced Academic Research Vol.1(1) 2014: 53-57